1988
DOI: 10.2224/sbp.1988.16.1.25
|View full text |Cite
|
Sign up to set email alerts
|

Schizotypal Estimators in Adolescence: The Concurrent Validity of the Risc

Abstract: The validation of questionnaires intended to identify the position of a subject along a normal/schizotypal/schizophrenic continuum has always been problematic. Schizophrenic patients are not good at completing questionnaire, and validation has to depend on the identification of "at risk" groups. Watt Grubb & Elenmeyer-Kimling (1982) found that the adolescent offspring of schizophrenics show the negative schizophrenic symptomology of interpersonal disharmony and emotional instability. The study reported here, u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1988
1988
2007
2007

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Rust et al (in press) looked at the relationship between the RISC and the Eysenck Personality Questionnaire (EPQ) (Eysenck and Eysenck 1976). A correlational analysis between the two scales in the sample of 608 Venezuelan university students (both scales in Spanish translation) showed that the RISC and EPQ Psychoticism have a rather low, although significant, correlation of .12.…”
Section: Validitymentioning
confidence: 99%
“…Rust et al (in press) looked at the relationship between the RISC and the Eysenck Personality Questionnaire (EPQ) (Eysenck and Eysenck 1976). A correlational analysis between the two scales in the sample of 608 Venezuelan university students (both scales in Spanish translation) showed that the RISC and EPQ Psychoticism have a rather low, although significant, correlation of .12.…”
Section: Validitymentioning
confidence: 99%
“…Additionally, RlSC scores correlated positively with the number of schizotypal symptoms in a group of chronically mentally ill individuals (Rust, 1989). Moreover, in a non-clinical college sample, Rust & Chiu (1988) found RlSC scores were significantly related to measures of interpersonal disharmony and emotional instability which have been found in the offspring of schizophrenics. The present study examined the concurrent validity of the RlSC with other self-report measures of schizophrenia-spectrum attributes within a non-clinical population.…”
mentioning
confidence: 75%
“…The Rust Inventory of Schizotypal Cognitions (RISC; Rust, 1988Rust, , 1989Rust & Chiu, 1988; was administered to all participants. The RISC is a psychometrically constructed, cognitively based short questionnaire for tapping the cognitive schizotypal dimension in the normal population.…”
Section: Methodsmentioning
confidence: 99%